The Social Sciences and Humanities, in Momentous Times: On the Role and the Contribution of Social Sciences and Humanities on the “Balanced Holism” between Development and Social Inclusion-Sustainability - Papadakis, Nikos (HAPSc Policy Briefs Series, 2025)
The present paper attempts a brief critical review of some of the key-aspects and facets of the (actual and potential) role and contribution of the Social Sciences and Humanities in a developmental paradigm combined with social inclusion and social sustainability. Initially, it briefly analyses the current state-of-play regarding the international trends and transformations in Politics, Economy and Labour Market, as well as of their impact (jointly with the impact of the permaciris) on the social cohesion and subsequently the Society-at-Large per se, within an, increasingly unstable, context. It lays special emphasis on issues related to precarity, social vulnerability, (intergenerational transmission of) poverty and uncertainty. Given that, it casts the light (via specific theoretical and research-based insights and cases) on the contribution of the humanities and social sciences in analyzing, contextualizing and interpreting the key parameters of the above-mentioned, while providing value & evidence-based responses to the rising key-challenges and (even) threats, towards a holistic sustainable development, that could safeguard the social cohesion and promote an actual (individual and collective- social)l well-being, in momentous times.